Physicians’ Approach to Their Liability for Arranging Legal Reports a Study on Inquiries - Tüzün, Birgül; Elmas, İmdat; Akkay, Erdem (The Bulletin of Legal Medicine, 1998)
Task to arrange legal report, which every physician is encountered with in his professional practices is difficult but of beneficial nature to law when fulfilled accurately. This study was attempted to inquire on problems, physicians are confronted with during arranging reports in legal cases, to be informed about their levels of knowledge related with the subject and to learn their attitudes when confronted with problems and to predict what precautions should be taken by determining insufficiencies. A form of inquiry was prepared in the study, which was comprised of 25 questions, and applied on 33 practitioners, 35 specialists, and 39 specialist-candidates, totally 107 physicians who were employed in the Medical Faculty, State Hospital, Emergency Unit, and Foundation Hospital in Istanbul. Among these who were inquired, 61.9% indicated that they were frequently encountered with the liability to arrange legal report in their professional lives, 95.2% stated that in cases of life-dan- ger they preperred to arrange a provisional report and 84.2% noted that this report should be arranged only in cases where life-danger might result in death definitely. 49-2% describe period to obviate usual occupation indicated in definite legal report as the period that elapses until medical cure is attained, while 9.5% defined as the period of total admission in a sanitary unit. 63.5% stated that they did not arrange this definite legal report as they considered it a duty forensic physicians were obliged to fulfill and 60.7% claimed that education on forensic medicine was not adequately given in the faculty from which they graduated. When the answers physicians gave in the inquiry were evaluated, it was concluded that such fundamental concepts as life-danger, or obviation of usual occupation which were included in the report were not adequately comprehended medically and legally and that physicians were not cognizant of their authorities and liabilities in arranging legal report, with the result that pre- and postgraduate forensic medicine educational programmes should be extensively applied.Key words: Forensic Medicine, Physician, Education
Keywords: forensic medicine; physician; education